DIFFERENCES BETWEEN LEADERS AND NONLEADERS IN THEIR PERCEPTIONS OF THE ORGANIZATIONAL COMMITMENT TO QUALITY - Abd El-Moneim A. El-Tohamy; Atef T. Al Raoush (European Scientific Journal, ESJ, 2015)
The objective of this study was to determine if there were any significant differences between hospital leaders and non-leaders in their perceptions of the organizational commitment to quality in the governmental accredited hospitals in Jordan. A survey instrument, designed to measure the level of organizational commitment to quality, questionnaire, was administered to the healthcare professionals in the five governmental accredited hospitals in Jordan. Study sample included 1290 employees. The response rate was 83.6 % of the total questionnaires distributed. Of the1079 respondents, 141 were leaders and 938 were non-leaders. Two sample T test was used to compare the responses between these groups. There were significant differences found between leaders and non-leaders in their perceptions of organization’s commitment to quality